2011
DOI: 10.1128/jvi.01969-10
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Tyrosine Kinase Inhibitors Block Multiple Steps of Influenza A Virus Replication

Abstract: Host signaling pathways play important roles in the replication of influenza virus, but their functional effects remain to be characterized at the molecular level. Here we identify two receptor tyrosine kinase inhibitors (RTKIs) of the tyrphostin class that exhibit robust antiviral activity against influenza A virus replication in cultured cells. One of these (AG879) is a selective inhibitor of the nerve growth factor receptor and human epidermal growth factor receptor 2 (TrkA/HER2) signaling; the other, tyrph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
132
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 124 publications
(141 citation statements)
references
References 59 publications
(88 reference statements)
8
132
1
Order By: Relevance
“…The treatment of cells with protein kinase inhibitors has been shown to interfere with different stages in the virus life cycle, including nuclear import, transcription, translation, nuclear export, and viral egress (109)(110)(111)(112)(113). Consistent with this, we found that a number of kinases and phosphatases were present in the interactome.…”
Section: Discussionsupporting
confidence: 75%
“…The treatment of cells with protein kinase inhibitors has been shown to interfere with different stages in the virus life cycle, including nuclear import, transcription, translation, nuclear export, and viral egress (109)(110)(111)(112)(113). Consistent with this, we found that a number of kinases and phosphatases were present in the interactome.…”
Section: Discussionsupporting
confidence: 75%
“…We and others have shown that host signaling pathways play important roles in the influenza viral life cycle (13)(14)(15)(16)(17)(18)(19)(20). Increasing evidence suggests that diverse receptor tyrosine kinases (RTKs) and downstream signaling pathways, such as epidermal growth factor receptor (EGFR), TrkA, Raf/MEK/ERK, and phosphatidylinositol 3-kinase (PI3K)/Akt, are involved in discrete steps of the influenza viral life cycle (13)(14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…Increasing evidence suggests that diverse receptor tyrosine kinases (RTKs) and downstream signaling pathways, such as epidermal growth factor receptor (EGFR), TrkA, Raf/MEK/ERK, and phosphatidylinositol 3-kinase (PI3K)/Akt, are involved in discrete steps of the influenza viral life cycle (13)(14)(15)(16)(17)(18)(19)(20). We have previously shown that TrkA activation is required for optimal viral RNA synthesis, vRNP export, and virus assembly and budding (17,18). Eierhoff et al have demonstrated that EGFR is activated by influenza A virus infection and facilitates its efficient cell entry (15).…”
mentioning
confidence: 99%
“…Interestingly, EGFR signaling and trafficking are also regulated by a number of other viruses, including hepatitis C virus (40), hepatitis E virus (7), human papillomavirus (55,58), and herpes simplex virus type-1 (38), and this pathway may regulate postentry steps in the viral life cycle, including viral RNA synthesis, nuclear export of vRNP, or release of virions (36). This finding underscores the notion that influenza virus may be susceptible to inhibition by smallmolecule inhibitors of EGFR tyrosine kinase activity (36), possibly including antitumor drugs such as gefitinib (37).…”
Section: Vol 85 2011mentioning
confidence: 99%